Mental Radio - Dongoski, Craig; Farina, Harrison (Critical Studies in Improvisation / Études critiques en improvisation, 2026)
This piece reflects research gleaned from the "Mental radio" course—which takes its title from the Upton Sinclair book of the same name—in which he tested and documented the telepathic capabilities of his wife Mary Claire Sinclair. "Mental radio" designates the transmission and reception of psychical content: intentions, images, or energies. The aim of the course is to explore mental radio as it applies to new modes of art-making. Our guiding principles have been expressivity, contingency, epiphany, precision, ritual, emergence, openness, and process. We are approaching the art-process from the mandate of intuition. What is in this article documenting the course is a testament to this process.